PENGARUH PENGGUNAAN MEDIA FLASHCARD AUGMENTED REALITY BERBASIS PENDEKATAN TPACK TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA KELAS IV SD GUGUS III KECAMATAN AMALI KABUPATEN BONE - Febrianti; Widya Karmila Sari Achmad; Faidah Yusuf (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is an experimental study aimed at determining whether there is an influence of using augmented reality flashcard media based on the TPACK approach on the critical thinking skills of fourth-grade students at Cluster III Amali District, Bone Regency. The approach used in this study is a quasi-experimental approach with a non-equivalent control group design. The population in this study consists of all fourth-grade students at Cluster III Amali, totaling 87 students. The samples in this study consisted of fourth-grade students from UPT SD Inpres 12/17 Mattaropurae totaling 23 students and UPT SD Negeri 131 Tocinnong totaling 20 students selected through purposive sampling technique. Data collection techniques include written tests conducted before and after treatment, and observation.Data analysis was conducted descriptively and inferentially using the Independent Sample t-test. The results of this study indicate that the use of augmented reality flashcard media based on TPACK is classified as good and can encourage active student engagement during the learning process. Students’ critical thinking skills showed a significant increase after the use of the media. The t-test results showed a significance value of <0.05, thus H0 is rejected and Ha is accepted. Therefore, it can be concluded that the use of augmented reality flashcard media based on the TPACK approach has a positive and significant effect on the critical thinking skills of fourth-grade elementary school students.